2011
DOI: 10.1186/1471-2407-11-398
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the rtA181T/sW172* mutant increased the risk of hepatoma occurrence in patients with lamivudine-resistant chronic hepatitis B

Abstract: BackgroundDevelopment of the hepatitis B virus (HBV) rtA181T/sW172* mutant could occur during prolonged lamivudine (LAM) therapy, conferring cross resistance to adefovir. Recent studies demonstrated an increased oncogenic potential of this mutant in NIH3T3 cells. In this study, we aimed to investigate the clinical significance of this finding.MethodsSerum samples from 123 LAM-resistant chronic hepatitis B patients were submitted for virological assays. A highly sensitive amplification created restriction enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…In view of HCC prevention, peginterferon remains superior to nucleos(t)ide analogs (9). One possible reason for this is the emergence of HBV surface antigen truncation mutations, which had increased oncogenic potentials, in patients receiving long-term nucleos(t)ide analogue therapy (9)(10)(11) and the other is the immunomodulatory properties of peginterferon, which is believed to exert anticancer effect (12).…”
Section: Abstract Background: a Lower Neutrophil-to-lymphocyte Ratiomentioning
confidence: 99%
“…In view of HCC prevention, peginterferon remains superior to nucleos(t)ide analogs (9). One possible reason for this is the emergence of HBV surface antigen truncation mutations, which had increased oncogenic potentials, in patients receiving long-term nucleos(t)ide analogue therapy (9)(10)(11) and the other is the immunomodulatory properties of peginterferon, which is believed to exert anticancer effect (12).…”
Section: Abstract Background: a Lower Neutrophil-to-lymphocyte Ratiomentioning
confidence: 99%
“…Bae reported that 58.2% of patients show complete antiviral responses using LAM in decompensated HBV-related cirrhosis, which can improve the clinical prognosis (Bae et al, 2005). However, the failure of antiviral treatment or drug resistance are dangerous factors for liver disease progression and increase the incidence of liver cancer (Yeh et al, 2011;Zoulim, 2011). A single randomized double-blind controlled trial of LAM in patients with HBeAg and/or high serum HBV DNA levels showed that antiviral therapy prevented disease progression and reduced the incidence of HCC Nishida et al, 2008).…”
Section: Et Al 2269mentioning
confidence: 99%
“…Some data supporting the benefit of antiviral therapy on the prevention of HCC in chronic hepatitis B patients has been shown in a few randomized controlled trials (Zhang et al, 2011;Jin et al, 2011;Lim et al, 2011;Tujios and Lee, 2012). Nonetheless, antiviral drug resistance is important in determining the success of long-term therapy for chronic hepatitis B patients (Yeh et al, 2011;Papatheodoridis et al, 2010). In recent clinical study data, the development of resistance to NUCs is associated with exacerbation of liver disease, including development of cirrhosis and HCC (Yeh et al, 2011), in addition, the risk of HCC remains high in HBV-related cirrhosis in patients who are treatment-naïve using NUCs (Papatheodoridis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pre-S mutants in serum sample was reported to carry a high risk of developing HCC (27,28). The oncogenic potential of HBV sW172 * was also confirmed through its ability to transactivate the cMyc and SV40 promoters (12,29). There are still no reports on the oncogenic potential of this mutant in initiating ER stress and oxidative damage.…”
mentioning
confidence: 99%